An Evaluation of the Solihull Approach Foster Carer Course. Issue 3 (27th May 2019) - Harris-Waller, Jayne; Bangerh, Priya; Douglas, Hazel
Abstract : This is an evaluation focusing on the effectiveness of the Solihull Approach foster carer training group programme 'Understanding your foster child'. Four groups were run, of 12 weekly sessions with a total of 56 foster carers. All foster carers who attended completed both pre and post measures, however incomplete data sets were removed, so in total 27 data sets were analysed. Four questionnaires were used: Parental Stress Index Short Form (PSI-SF), Strengths and Difficulties Questionnaire (SDQ), Carer Questionnaire and the Children's Expression of Feelings in Relationships (CEFR). Statistical analyses identified that after the group, there were significant increases in foster carers' ratings of their understanding of their children's difficulties; their understanding of why foster children behaved the way they did; their feeling of having the required skills to manage difficulties; alongside significant decreases in their ratings of foster children's hyperactivity and attentional behaviour difficulties.